TRANSPARENCY AND ACCOUNTABILITY OF PRODUCTIVE WAQF: MITIGATING THE PRINCIPAL-AGENT PROBLEM THROUGH THE SHARIA CORPORATE SOCIAL PERFORMANCE (CSP) FRAMEWORK - Muhammad Azrul Amirullah; M. Akbar Hilman; Muhammad Nabil Hanif; Musyaffa Addin (Jurnal Ilmiah Al-Tsarwah, 2025)
Economic empowerment in the modern era focuses not only on improving material well-being but also demands equity, distributive justice, and social sustainability in accordance with sharia principles. In this context, waqf becomes a strategic instrument. The Indonesian Waqf Board (BWI, 2023) estimates that the potential for cash waqf in Indonesia reaches around IDR 180 trillion per year, but its realization is still very low, only in the range of several trillion rupiah. This large gap indicates that the potential of waqf as an inclusive and sustainable long-term financing instrument has not been optimally utilized. Using a descriptive qualitative method, a case study on the Foundation for the Maintenance and Expansion of Waqf at Pondok Modern Gontor (YPPWPM), UNIDA Gontor will be complemented by in-depth semi-structured interviews with various stakeholders to map perceptions and analyze relevant documents. Findings indicate persistent information asymmetry and limited public reporting, which erode trust and constrain the productivity of waqf assets. Mapping CSP’s three pillars: (i) social responsibility principles, (ii) social responsiveness processes, and (iii) observable outcomes onto YPPWPM’s governance clarifies where accountability mechanisms can be operationalized (e.g., clearer role separation, auditable reporting, outcome tracking aligned to maqāṣid al-sharī‘ah). The paper proposes a practicable CSP-Syariah checklist for nazhir that reduces information asymmetry, strengthens answerability, and improves legitimacy, thereby mitigating the principal–agent problem and enabling more consistent productive deployment of waqf assets at Gontor. Policy and managerial implications highlight the need for standardized public reporting, routine sharia/audit reviews, and outcome-based monitoring to sustain stakeholder confidence and social